The Role Of Bcsa Gene In Cellulose Biosynthesis Of Burkholderia Pseudomallei - Chai , Muh Chyi (2010)

(untitled)
Two copies of cellulose synthase gene were identified in the genome database of B. pseudomallei K96243. Both genes are located on the chromosome II and labelled as open reading frame (ORF) BPSS0735 and BPSS1577, respectively. Sequence comparisons revealed that the two genes share low similarity and identity of 35% and 24%, respectively. This suggested that the two cellulose synthase genes are of different origins. In this study, B. pseudomallei was investigated for the biosynthesis of cellulose and experimental evidences of the presence of cellulose were shown. Hence, a study was conducted to characterize the role of BPSS1577 (also annotated as bcsA) in the cellulose biosynthesis of B. pseudomallei. A bcsA deleted mutant was generated to determine whether bcsA was involved in biofilm formation, adherence to abiotic surfaces and desiccation survival potential in this bacterium.